Phosphorylation of NANOG by casein kinase I regulates embryonic stem cell self‐renewal. Issue 1 (18th November 2020) - Mullin, Nicholas P.; Varghese, Joby; Colby, Douglas; Richardson, Julia M.; Findlay, Greg M.; Chambers, Ian
Abstract : The self‐renewal efficiency of mouse embryonic stem cells (ESCs) is determined by the concentration of the transcription factor NANOG. While NANOG binds thousands of sites in chromatin, the regulatory systems that control DNA binding are poorly characterised. Here, we show that NANOG is phosphorylated by casein kinase I, and identify target residues. Phosphomimetic substitutions at phosphorylation sites within the homeodomain (S130 and S131) have site‐specific functional effects. Phosphomimetic substitution of S130 abolishes DNA binding by NANOG and eliminates LIF‐independent self‐renewal. In contrast, phosphomimetic substitution of S131 enhances LIF‐independent self‐renewal, without influencing DNA binding. Modelling the DNA–homeodomain complex explains the disparate effects of these phosphomimetic substitutions. These results indicate how phosphorylation may influence NANOG homeodomain interactions that underpin ESC self‐renewal. Abstract :